PCOS In Females is independent of Ferritin and Minerals Levels (Journal of Pharmaceutical Negative Results, 2022)
Females of reproductive age may be affected by a complex endocrine disorder called, Polycystic Ovary Syndrome (PCOS). One of the intracellular proteins is Ferritin, have a role in regulating iron homeostasis. This study was planned to investigate the association between serum ferritin levels with blood calcium levels and some other minerals in Iraqi females with PCOS. Ferritin and some minerals were measured in sixteen Iraqi patients with PCOS. The level of ferritin was assessed in serum by ELISA technique. The level of serum ferritin displayed normal value in patients. Among patients with PCOS, the level of ferritin revealed a non-significant relationship with calcium in the disease. The study concludes that among polycystic ovarian patients, ferritin concentrations are independent of age, BMI, waist/ hip ratio, serum potassium, and ionized serum calcium which may point out that the exact reason for PCOS is still unidentified.